Deformable and wearable carbon nanotube microwire-based sensors for ultrasensitive monitoring of strain, pressure and torsion. Issue 2 (12th December 2016) - Zhou, Jian; Xu, Xuezhu; Yu, Hu; Lubineau, Gilles
Abstract : A sensor is a promising alternative to conventional mechanical sensors combining an easy fabrication process, multi-mode deformation detection, high sensitivity, excellent durability and reusability. Abstract : Human joints have the ability to recover their mechanical functions after moderate dislocation. This remarkable capability inspired us to develop a "bone-skin-like" mechanosensor that can detect multiple mechanical deformations after recovery from electrical disconnection. To create this sensor, we embedded a low-strength, wet-spun single-walled carbon nanotube wire in polydimethylsiloxane. When various mechanical stimuli are applied, the wire gets fragmented and its resistance increases dramatically (from 360 Ω to practically infinity) in a reversible, recoverable manner even after the electrical failure/disconnection. The sensor is sensitive enough (a gauge factor of 10 5 at 15% uniaxial strain, a pressure sensitivity of 10 5 MPa −1 at 0.9 MPa pressure and a torsion sensitivity of 860 at a twisting angle of 60°) to be used for accurate sensing of a variety of deformation modes, suggesting a wide range of applications in wearable and deformable mechanical sensors.